The Role Of MRI In Early Detection Of Neurodegenerative Diseases (The Review of Diabetic Studies, 2025)
Background: Magnetic Resonance Imaging (MRI) is a cornerstone non-invasive modality for the early detection and ongoing monitoring of neurodegenerative diseases. Given its capacity to provide detailed insights into cerebral structural and functional alterations, MRI is a highly sensitive component within multimodal diagnostic frameworks.Objectives: This study was designed to investigate the diagnostic efficacy of MRI for the early identification of neurodegenerative diseases and to elucidate its potential clinical applications.Methods: We conducted a cross-sectional study involving a cohort of 114 participants. The final sample consisted of 57 patients with early-stage neurodegenerative disease and 57 healthy controls. The patient subgroup was comprised of 24 individuals with early-stage Parkinson's disease (42.1%) and 33 with early-stage Alzheimer's disease (57.9%). MRI-based quantitative analysis was employed to identify and compare structural and functional metrics between the two cohorts.Results: The patient group demonstrated a 13.9% reduction in hippocampal volume compared to the controls (p